The disease burden of pneumoconiosis in China from 1990 to 2021 and projection to 2050 based on GBD 2021: a cross-sectional study - Gong, Xiangwen; Cui, Kaiwang; Liu, Zhi; Tang, Yongtong; Li, Jingbo; Chen, Youmei; Tu, Zhangshun; Yuan, Miaomiao; Liu, Jianping; Wu, Haiwu (Frontiers in Public Health, 2025)
BackgroundPneumoconiosis is a serious occupational disease with high incidence and prevalence in China. This study aimed to describe the long-term trends in the burden of pneumoconiosis and its epidemiological characteristics in China over the past 30 years.MethodsData from this cross-sectional study were obtained from the Global Burden of Disease (GBD) 2021 study. Joinpoint was used to calculate the annual average percentage change (AAPC), and age–period–cohort (APC) analyses were used to assess trends in the burden of pneumoconiosis. The Bayesian age-period-cohort (BAPC) model was used to forecast pneumoconiosis burden from 2022 to 2050.ResultsFrom 1990--2021, the age-standardized incidence rate (ASIR) and mortality rate (ASMR) of pneumoconiosis in China declined from 2.2 (1.83, 2.59) to 1.42 (1.21, 1.63) and from 0.9 (0.73, 1.09) to 0.41 (0.32, 0.53) cases per 100,000 people. The AAPCs of the ASIR and ASMR were −1.42% and −2.15%, respectively. The age-standardized disability-adjusted life years (DALY) and years of life lost (YLL) also decline from 24.32 (20.05, 29.47) to 10.86 (8.49, 13.87) and from 22.39 (18.13, 27.51) to 9.38 (7.1, 12.32) years per 100,000 persons. APC analyses revealed that the incidence and mortality risk of pneumoconiosis increased with age, decreased with period, and were greater in the early birth cohort. From 2022 to 2025, the ASIR and ASPR are expected to remain relatively stable, while the ASMR is projected to decline significantly to 0.267/100,000 in 2050.ConclusionDespite the downward trend in age-standardized disease burden indicators of pneumoconiosis, the burden of pneumoconiosis remains heavy due to the large occupational population in China.